Association between non-academic activities and professional identity formation of Indonesian medical students: a nationwide cross-sectional study - Sydney Tjandra; Arnold Keane; Defin Allevia Yumnanisha; Mukhlis Akmal Taher; Hansel Andita Kristiandi; Anyta Pinasthika; Nadia Greviana (Korean Journal of Medical Education)
Purpose This study explores the association between student involvement in non-academic activities (NAA) and the stages of professional identity formation (PIF) among Indonesian medical students. Methods This cross-sectional survey was distributed to students in 50 medical schools, across both preclinical and clinical students in years 2-6. Respondents completed a Developmental Scale (DS) questionnaire to assess PIF and self-reported the number of hours spent on different NAA. Descriptive and bivariate analyses were performed; multiple linear regression was utilized to predict PIF. Results Indonesian medical students reported a median of 13 NAA hours and a median DS score of 5.07 on a scale of 7. NAA hours were significantly different across sex groups, years of study, university regions, and institution types. Female participants spent significantly more hours on NAA than male students and PIF was predicted by the number of hours spent on research and competition-related activities. Shifts between the types of NAA were also observed among year groups. Conclusion NAA are positively associated with the PIF process, with students’ active involvement in research and competitionrelated activities as predictors in this area. Supporting these activities becomes imperative for medical schools in order to optimize students’ potential, motivation, and PIF.